PEMBERDAYAAN KELOMPOK TANI ETAWA MELALUI PELATIHAN DAN PENDAMPINGAN KANDANG RAMAH LINGKUNGAN DI KAMPUNG BENUA RAJA KECAMATAN RANTAU KABUPATEN ACEH TAMIANG - Heri Irawan; Irwansyah Irwansyah; Faiz Isma (Global Science Society, 2020)
The proposed Community Partnership Program will provide solutions and innovations about effective, easy, efficient and environmentally friendly enclosure systems. Technological innovation in making this cage is the existence of a separator between solid and liquid impurities as a source of odor and the existence of a control tub to accommodate liquid impurities so that it spreads. The Community Partnership Program activities will be carried out for 6 months. The target of this activity program is the Etawa Farmers Group located in Benua Raja Village. The main problem faced by Mitra is that the goat livestock business is undergoing very rapid development, but the waste generated both solid and liquid has not been managed optimally and is still scattered around the cage, causing unpleasant odors. Activities to be carried out during the Community Partnership Program on Mitra1; Training and mentoring environmentally friendly goat pens. The activity continued with Partner 2. Training and making a control tub to collect liquid waste that has a high economic value. The targets of the Community Partnership Program are; produce environmentally friendly pens Community Partnership Program (PKM) is the publication of scientific articles